Orgins of totalitarianism. - "Arendt,Hannah." (New York, 1960)
This movement of anticipation is like the calm that settles after all hopes have died. We no longer hope fro an eventual restoration of the old world order with all its traditions, or for the reintegration of the masses of five continents who have been thrown into a chaos produced by the violence of wars and revolutions and the growing decay of all that has still been spared.
Keywords: Political science